Implementation of Military Barracks-Based Education in Arabic Language Learning for Military Personnel - Mia Nurmala; Iqlima Najmi Amalia Anandiar; Keysha Shira Zafirah; Nurul Fadhilah; Muhsin Muis (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study examines the implementation of barracks-based education in Arabic language learning for military personnel, focusing on its implementation in supporting the acquisition of Arabic language proficiency. Arabic language learning for military-specific purposes requires an approach that integrates linguistic competence with a specialized curriculum within the framework of military education. The study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and analysis of curriculum documents and instructional materials. The findings indicate that Arabic language learning is integrated with the Three Basic Patterns of Military Education, encompassing attitude and behavior development (10%), Arabic language knowledge and skills development (80%), and military physical development (10%). These three dimensions operate simultaneously within a dormitory-based system over a 12-week period, totaling 600 instructional hours. At the operational level, the implementation demonstrates synergy among military instructors with their multiple roles, learners with their internal motivation, and the Al-'Arabiyyah Baina Yadaik instructional materials, all of which contribute to the gradual and integrated acquisition of Arabic language skills. In addition, challenges were identified, including the heterogeneity of learners' educational backgrounds and the limited availability of contextual instructional materials that accommodate diverse proficiency levels.